1997
DOI: 10.2307/3284254
|View full text |Cite
|
Sign up to set email alerts
|

Studies on a Primaquine-Tolerant Strain of Plasmodium vivax from Brazil in Aotus and Saimiri Monkeys

Abstract: A nonimmune American acquired an infection of Plasmodium vivax Type 1 malaria in Brazil in 1994. After returning to the U.S.A., he had a primary attack followed by 3 relapses. The primary attack and first 2 relapses were treated with a standard regimen of chloroquine, followed by 14 days of primaquine (15 mg/day). Following the third relapse, the primaquine treatment was extended to 28 days. No further relapses occurred. The lack of response to primaquine by this strain may recommend it as a suitable candidate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
22
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 50 publications
1
22
0
Order By: Relevance
“…8,9 Since then, reports of primaquine resistance or primaquine failure have become fairly common from areas such as Papua New Guinea, Southeast Asia, India, and Colombia. [3][4][5][6][7][10][11][12] These five cases originating in Ethiopia support other reports suggesting that the incidence of P. vivax malaria in east Africa, and its failure to respond to standard doses of primaquine in this area, may actually be higher than suspected. 1,2 Relapses despite primaquine treatment may reflect changes in primaquine response among formerly susceptible strains, or geographic spread of strains that have long been known to be refractory.…”
supporting
confidence: 67%
See 1 more Smart Citation
“…8,9 Since then, reports of primaquine resistance or primaquine failure have become fairly common from areas such as Papua New Guinea, Southeast Asia, India, and Colombia. [3][4][5][6][7][10][11][12] These five cases originating in Ethiopia support other reports suggesting that the incidence of P. vivax malaria in east Africa, and its failure to respond to standard doses of primaquine in this area, may actually be higher than suspected. 1,2 Relapses despite primaquine treatment may reflect changes in primaquine response among formerly susceptible strains, or geographic spread of strains that have long been known to be refractory.…”
supporting
confidence: 67%
“…2 Reports of primaquine failures have also increased, primarily from Papua New Guinea, Southeast Asia, and Central and South America. [3][4][5][6][7] Relapses following primaquine treatment of strains acquired in Africa have been less well described.…”
mentioning
confidence: 99%
“…Gascon et al (86) described two cases of primaquine failure from Guatemala who were treated in Spain. Finally, Nayar et al (155) described the primaquine-resistant Brazil I/CDC strain of P. vivax coming from a traveler infected in Brazil who failed three separate courses of 15 mg daily for 14 days but finally succeeded with that regimen after it was administered over 28 days. Vivax malaria from South America appears to respond poorly to the 15-mg (14-day) regimen, and the 30-mg regimen should be applied.…”
Section: Distributionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9] As a result, these monkey species have been used successfully for preclinical assessment of malaria vaccine candidates targeting parasite blood stages, [10][11][12] as well as for the assessment of new antimalarial lead compounds. 3,13,14 However, infection by sporozoites has generally been more difficult to achieve. Previous studies have shown that several types of some Aotus species can be infected with sporozoites from P. vivax strains previously adapted to grow in monkey blood, although they have more prolonged prepatent periods than the Saimiri model.…”
Section: Introductionmentioning
confidence: 99%